Epidemiology of HIV and Tuberculosis in pregnant women, South West Nigeria - Glory Atilola; Taiwo Randle; Tomisin Obadara; Isaac O. Komolafe; Gbenga Odutolu; Josephine Olomu; Laide Adenuga (Elsevier, 2018)
Background: Pregnant women remain the most vulnerable high-risk population to the devastating impact of the on-going human immunodeficiency virus (HIV) generalized epidemic and co-infection with Tuberculosis in Nigeria. By the end of 2017, the country ranked the second highest in adult HIV-infected individuals and the highest population of orphans due to AIDS in sub-Saharan Africa. We assessed the epidemiology of HIV among pregnant women across ten facilities in south-west Nigeria. Methods: This is a cross-sectional study design in which 353 pregnant women randomly selected across ten health care facilities in two states in south west Nigeria. This study was conducted between January and May 2015. HIV testing was conducted and active tuberculosis screening was implemented using the fluorescence microscopy. In addition, a structured questionnaire was administered to elicit risk factors of HIV infection and syndromic Tuberculosis in the study population. Results: We found a 5.1% (18/353:95% CI:3.0%-8.0%) rate of HIV and 0% active tuberculosis in the study population. HIV positive pregnant women were 6 times more likely to have blood transfusion with greater odds of infection found in pregnant women with history of blood transfusion in the previous three months (OR:3.27, 95% CI:0.44-24.36). Pregnant women who tested HIV negative had 70% reduction in odds of infection (OR:0.21:95% CI:0.06-0.77). Conclusions: This study suggests a possible strong epidemiological link between HIV infection and recent blood transfusion among pregnant women attending ante-natal clinics in south west Nigeria. We therefore recommend further study to develop a more robust estimate of blood transfusion and the risk of HIV in pregnant women in Nigeria. Keywords: HIV, Epidemiology, Pregnant, Women, Nigeria